2015
DOI: 10.1088/1674-1056/24/1/014204
|View full text |Cite
|
Sign up to set email alerts
|

Role of incoherent pumping and Er 3+ ion concentration on subluminal and superluminal light propagation in Er 3+ -doped YAG crystal

Abstract: We study the absorption-dispersion process and group index of weak probe field in a four-level Er 3+ :YAG crystal. We find that the Er 3+ ion concentration and incoherent pumping field can influence the absorption-dispersion process and group index of weak probe field. Moreover, our results show that Er 3+ ion concentration plays a major role in lasing without inversion and absorption with inversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 86 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Zharikov et al first observed the stimulated emission from Er 3 + ions in the YAG crystal [45]. Since then many kinds of quantum optical phenomena have been studied in Er 3 + -doped YAG crystal, such as electromagnetically induced transparency [46], large refractive index without absorption [47], lasing without inversion [48], subluminal and superluminal light propagation [49], giant Kerr nonlinearity [50], optical bistability [51,52] and electromagnetically induced grating [53]. So far, to the best of our knowledge, studies have not been extended to the investigation of the coherent control of GH shift in an Er 3 + -doped YAG crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Zharikov et al first observed the stimulated emission from Er 3 + ions in the YAG crystal [45]. Since then many kinds of quantum optical phenomena have been studied in Er 3 + -doped YAG crystal, such as electromagnetically induced transparency [46], large refractive index without absorption [47], lasing without inversion [48], subluminal and superluminal light propagation [49], giant Kerr nonlinearity [50], optical bistability [51,52] and electromagnetically induced grating [53]. So far, to the best of our knowledge, studies have not been extended to the investigation of the coherent control of GH shift in an Er 3 + -doped YAG crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, slow and fast light via twowave mixing in an ytterbium-doped fiber at 1064 nm were investigated in detail [14]. In 2015, Asadpour et al showed that the reflected and transmitted pulses can be tuned from subluminal to superluminal at different wavelengths by changing the spin coherence in the defect dielectric medium [15]. Wang shows that the higher input power or higher optical gain is better for optical signal processing and optical telecommunications [16].…”
Section: Introductionmentioning
confidence: 99%
“…While it is known that negative group delay is found in many types of circuits and medium [7][8][9][10][11][12], it was initially unclear if negative propagation of signal occurs in such circuits or medium. Indeed, to date, several studies have revealed that negative group delay is not involved with the negative propagation of signal [13][14][15] and that the observed negative propagation is the result of signal distortion.…”
Section: Introductionmentioning
confidence: 99%